Autistic Spectrum Disorder and Assistive Technology: Action Research Case Study of Reading Supports - Gentry, James E.; Lindsey, Pam (Journal of the American Academy of Special Education Professionals, 2012)
This descriptive action research experience with case study procedures examined the use of best practices paired with assistive technologies as interventions to individualize fiction reading instruction for a high-functioning elementary student, JB (pseudonym), diagnosed with autistic spectrum disorder. JB’s instructional, reading goals were to correctly indentify (a) unknown vocabulary words, (b) words with multiple meanings, (c) idiom phrases, and (d) comprehend main story grammar elements within a fictional story line. Also, JB’s teachers wanted to see if JB understood (e) characterization within a fictional story. JB’s experience reading a fictional text with assistive technological support to accomplish reading skill objectives is described and evaluated by his teachers and researchers.